Innovation of Public Services Reviewed from Community Satisfaction Index to The District of Banyuwangi - Lilik Herawati (Ridwan Institute, 2022)
Community service innovations that have been stipulated in the Regulation of the Minister of PANRB No. 30/2014, is a breakthrough in the type of public service, starting from creative, original, and modified ideas which are principally implemented in the form of services that benefit the community, either directly or indirectly. The current innovation is carried out as a development of public service patterns which are not only measured from the assessment of the central government to the regions, but also from the community satisfaction index as regulated in Permenpan No. 16 of 2014 concerning the survey of community satisfaction with services and No. 14 of 2017 concerning the preparation of the community satisfaction index. The purpose of this study was to measure community service innovation by reviewing the community satisfaction index at the sub-district office service in Banyuwangi Regency. Research using this survey method uses research instruments using questionnaires distributed to 724 people taken from service recipient communities between 2019 and 2021 who are in 15 sub-districts (total 25 sub-districts) in Banyuwangi Regency. The survey results show that there is an intercorrelation between the innovation process of community services and the level of community satisfaction. Every aspect of service innovation undergoes development and its implementation is always followed by the level of community satisfaction.